A comparative study on child pornography law in Malaysia with special reference to the position in Canada / 'Awatif Azhari, Nabihah Atirah Md Bazli and Nurul Asikin Abdul Rahim - Azhari, 'Awatif; Md Bazli, Nabihah Atirah; Abdul Rahim, Nurul Asikin (2014)
This paper is a study on the law of child pornography in Malaysia with special reference on the legal position in Canada. As stated in Chapter 2, there is no specific provision with regard to the offence of child pornography in Malaysia. It was indeed covered under Section 292 of Penal Code but it is more on a general basis of obscenity without no mentioning of child pornography in a specific notion under its legislation. Therefore, the need to amend section 292 of Penal Code to include specific provision on child pornography is measured by looking at the current circumstantial evidence and by referring the law in Canada. The position of the law on child pornography from the global perspective have been laid down in Chapter 2 and it is submitted that numerous conventions being held to discuss this issue and many countries have specifically legislated the said law. Chapter 3 discuss about the current legal position with regards to child pornography in Malaysia whereas in Chapter 4, the law on child pornography that was applied in Canada were critically being examined and served as a model for the same law to be adapted in Malaysia. The opinions from individuals that had been interviewed on the need to amend and to have a specific law on of child pornography have been compiled under Chapter 5 of this paper. Meanwhile, the recommendations and conclusions with regards to this study is provided under Chapter 6.